Pengaruh Sikap, Kondisi Pendukung dan Kompleksitas Teknologi Informasi Terhadap Kinerja Organisasi - Rika Kharlina Ekawati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2015)
Information technology is one of the things that are important in supporting the operational success of an organization. In an uncertain environment, information becomes a necessity especially to support organizational performance to make a decision. A combination of human, hardware, software and communication network resource data, which collects change, and disseminate information within an organization to support decision making and control the organization it is important to note in the application of information technology. Taking a case study at the Islamic State University (UIN) Raden Fatah Palembang, this study applied the Model of PC Utilization that suppose to find empirical evidence that there is influence between attitude, supporting conditionsand complexity of information technology on performance of the organization. By using regression analysis to be done, the results obtained show that significant yields of attitude variables 0.005 and supporting condition with significant levels of 0.011 which means smaller than 0.05 second so that this variable is declared to have an effect on organizational performance. While the complexity of information technology has no influence because the resulting significant of 0.235 based regression test used in this study.